2013
DOI: 10.1002/ibd.22948
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis on the Effects of Thiopurines on Birth Outcomes from Female and Male Patients with Inflammatory Bowel Disease

Abstract: Thiopurine exposure in women with IBD was not associated with LBW or congenital abnormalities, but was associated with preterm birth. Exposure in men at the time of conception was not associated with congenital abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
139
3
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 210 publications
(146 citation statements)
references
References 60 publications
1
139
3
3
Order By: Relevance
“…AZA and 6-MP both target the expansion of T lymphocytes, and suppress lymphocyte survival to depress inflammatory responses in IBD. These drugs effectively establish and maintain remission of IBD and are especially helpful in patients who have do not respond strongly to milder therapies (such as aminosalicylates), or are steroid-dependent [112] . There are variable and conflicting data on side effects of immunomodulators in humans.…”
Section: -Mp/azamentioning
confidence: 99%
See 4 more Smart Citations
“…AZA and 6-MP both target the expansion of T lymphocytes, and suppress lymphocyte survival to depress inflammatory responses in IBD. These drugs effectively establish and maintain remission of IBD and are especially helpful in patients who have do not respond strongly to milder therapies (such as aminosalicylates), or are steroid-dependent [112] . There are variable and conflicting data on side effects of immunomodulators in humans.…”
Section: -Mp/azamentioning
confidence: 99%
“…It was also found that there was a risk for increased preterm deliveries, LBW, and "small for gestational age" babies in AZA treatment associated pregnancies. A meta-analysis performed in 2012 showed that men fathering children who were exposed to thiopurine around the time of conception did not increase rates of congenital birth defects and so did not recommend discontinuation of treatment in men [112] . However, if there is a medical history of unexplained infertility or miscarriages, men should discontinue taking thiopurines at least four months before conception to improve fertility [114] .…”
Section: -Mp/azamentioning
confidence: 99%
See 3 more Smart Citations